You can do that?!: Feasibility of virtual reality exposure therapy in the treatment of PTSD due to military sexual trauma. (January 2019) - Loucks, Laura; Yasinski, Carly; Norrholm, Seth D.; Maples-Keller, Jessica; Post, Loren; Zwiebach, Liza; Fiorillo, Devika; Goodlin, Megan; Jovanovic, Tanja; Rizzo, Albert A.; Rothbaum, Barbara O.
Highlights: Virtual reality exposure therapy (VRE) is safe in treating MST-related PTSD. Participant engagement and retention rates are consistent with other EBTs for PTSD. Initial evidence suggests VRE reduces PTSD and depression symptoms due to MST. Abstract: This initial feasibility study examined the use of virtual reality exposure therapy (VRE) in the treatment of MST-related PTSD, with newly developed content tailored to MST. Participants included 15 veterans (26% male) with MST-related PTSD. Assessment of PTSD, depression, and psychophysiological indicators of distress occurred at pre-treatment, post-treatment, and 3-month follow-up. Treatment included 6–12 VRE sessions. There were significant reductions in pre- to post-treatment PTSD (CAPS severity: t(10) = 3.69, p = .004; PCL-5: t(10) = 3.79, p = .004) and depressive symptoms, (PHQ-9: t(8) = 2.83, p = .022), which were maintained at follow-up. There also was a significant pre- to post-treatment reduction in heart rate response to a trauma cue. Cohen's d effect sizes were large (CAPS: d = 1.11; PCL-5: d = 1.14, PHQ-9: d = .94), and the percentage of participants meeting PTSD criteria continued to decline from post-treatment (53%) to follow-up (33%). Findings indicate VRE can be safely delivered and is a promising treatment for MST-related PTSD.